2009
DOI: 10.1292/jvms.71.931
|View full text |Cite
|
Sign up to set email alerts
|

Deposition Process of Eosinophilic Substance in Mouse Nasal Septum

Abstract: ABSTRACT. An eosinophilic substance is usually observed in the mouse nasal septum, and its volume increases with age. In contrast to descriptions in textbooks defining the eosinophilic substance as amyloid, our previous report revealed that the observed eosinophilic substance is not amyloid, but consisted of collagen and an amorphous material. Furthermore, it was suggested that the amorphous material was produced by the clear hematoxylin and eosin (HE)-stained nasal gland epithelial cells. In this study, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Similar lesions were previously diagnosed as an “eosinophilic substance” 11 , 12 , 13 . The material was reported to be Congo red negative, pale blue with Masson’s trichrome and dark magenta with PAS.…”
Section: Nasal Septum Hyalinosis/eosinophilic Substancesupporting
confidence: 62%
See 1 more Smart Citation
“…Similar lesions were previously diagnosed as an “eosinophilic substance” 11 , 12 , 13 . The material was reported to be Congo red negative, pale blue with Masson’s trichrome and dark magenta with PAS.…”
Section: Nasal Septum Hyalinosis/eosinophilic Substancesupporting
confidence: 62%
“…After the presentation, there was discussion about whether or not to rename this lesion as “nasal septum hyalinosis,” since it has already been reported in the literature three times as “eosinophilic substance” by Doi et al 11 , 12 , 13 A revote resulted in nasal septum hyalinosis (48%), eosinophilic substance (46%), nasal gland proteinosis (3%), interstitial hyalinosis (2%), nasal gland secretion (2%), amyloid (0%) and others (0%). These voting results indicate that all audience members agreed that this lesion was not amyloid, although this is the diagnosis in the current INHAND document 14 .…”
Section: Nasal Septum Hyalinosis/eosinophilic Substancementioning
confidence: 99%
“…This lesion has been previously diagnosed as “eosinophilic substance” (ES) (Doi et al 2007, 2009, 2010). Present within the mouse nasal septum, it increases in volume with age (which plateaus over time), is more intense in males, and is not associated with degeneration or inflammation.…”
Section: What Is That Eosinophilic Material?mentioning
confidence: 99%
“…ES deposited at the interstitium of the clear HE-stained nasal glands only. Additionally, electron microscopic findings suggested that the amorphous material, which is a major component of ES, was produced by the clear HE-stained nasal gland epithelial cells and migrated to the interstitium through the partial opening of the basement membrane (Doi et al 2007(Doi et al , 2009. The amorphous material is probably produced physiologically, because ES was found in all mice (Doi et al 2007;Engelhardt, Gries, and Long 1993;Leininger, Herbert, and Morgan 1996), and neither nasal gland degeneration nor inflammation occurred even when the grade of ES deposition was enhanced (Doi et al 2007), but the significance of ES is not clear.…”
Section: Introductionmentioning
confidence: 99%